A higher loyalty : truth, lies, and leadership - Comey, James B., Jr., 1960- (Flatiron Books, 2018)
Former FBI director James Comey shares his experiences from his two decades in government, exploring what good, ethical leadership looks like, and how it drives sound decisions. His journey provides an entry into the corridors of power and a lesson in what makes an effective leader. Mr. Comey served as director of the FBI from 2013 to 2017, appointed to the post by President Barack Obama. He previously served as U.S. attorney for the Southern District of New York and as the U.S. Deputy Attorney General in the administration of President George W. Bush. From prosecuting the Mafia and Martha Stewart to helping change the Bush administration's policies on torture and electronic surveillance, overseeing the Hillary Clinton e-mail investigation as well as ties between the Trump campaign and Russia, Comey has been involved in some of the most consequential cases and policies of recent history.